Planning nodes, places, and pedestrian experiences in mountainous cities: an empirical transit station assessment tool - Yang, Yuanxiang; Yan, Shuiyu; Cong, Cong; Tian, Yu; Liu, Wen (Frontiers in Sustainable Cities, 2024)
In the context of ongoing discussions in Chongqing (China) about urban development strategies for the city's transit system, this paper introduces an empirical framework for assessing the development of urban transit stations in mountainous cities. Cities in mountainous areas possess unique natural topography, development patterns, cultures, and natural resources, leading to distinct urban development characteristics compared to cities built on plains. Drawing on the node-place modelling literature, we develop a multi-dimensional station assessment methodology adapted for mountainous cities. By adding the dimension of pedestrian experience, we propose indicators that represent the unique challenges of accessing stations in such terrains that are not typically reflected in conventional node-place analysis. Our findings reveal station-specific development opportunities in greater detail and can guide more targeted planning for land use around stations. Our assessment method is particularly useful for cities facing terrain challenges that impact pedestrian experience.